Atomistic modeling of pileup process in metal deposition manufacture - Mehrdad Shahmohammadi Beni; Tzu Hsien Tan; K.N. Yu (Results in Physics, 2019)
In present work, molecular dynamics (MD) simulation was employed to model the impact of single and double molten aluminum drops onto to an aluminum substrate. The study was related to the pileup process in metal deposition manufacture. Most previous investigations used the continuum scale Volume-of-Fluid (VOF) method to model this phenomenon. Here, the underlying mechanism of pileup process was examined in more details. The effect of impact speed on the height and width of the solidified drops was studied. The penetration depth of molten drops into the solid substrate was also investigated. The present model would be useful for future investigations as the process could now be studied at the atomic scale and the final solidified structure could also be assessed in terms of its defect and crystallinity. Keywords: Molecular dynamics, Pileup, Metal deposition, Atomistic modeling